Answer:
The correct answer is D. y = -3x – 1
Step-by-step explanation:
Let's find which of the following equations describes the relationship.
Answer A.
y = -x – 3
If x = 0 ⇒ y = -3; if x = 2 ⇒ y = - 5
Therefore, this is not the correct equation.
Answer B.
y = 3x - 1
If x = 0 ⇒ y = -1; if x = 2 ⇒ y = 5
Therefore, this is not the correct equation.
Answer C.
y = x – 3
If x = 0 ⇒ y = -3; if x = 2 ⇒ y = - 1
Therefore, this is not the correct equation.
Answer D.
y = -3x - 1
If x = 0 ⇒ y = -1; if x = 2 ⇒ y = - 7; if x = 5 ⇒ y = -16
Therefore, this is the correct equation.